2014
DOI: 10.3389/fnbeh.2014.00110
|View full text |Cite
|
Sign up to set email alerts
|

Medial prefrontal cortex: genes linked to bipolar disorder and schizophrenia have altered expression in the highly social maternal phenotype

Abstract: The transition to motherhood involves CNS changes that modify sociability and affective state. However, these changes also put females at risk for post-partum depression and psychosis, which impairs parenting abilities and adversely affects children. Thus, changes in expression and interactions in a core subset of genes may be critical for emergence of a healthy maternal phenotype, but inappropriate changes of the same genes could put women at risk for post-partum disorders. This study evaluated microarray gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 103 publications
(128 reference statements)
5
37
0
Order By: Relevance
“…This finding is consistent with enrichment analysis within specific regions (Eisinger et al, 2013b, 2014; Driessen et al, 2014b; Zhao et al, 2014) and suggests that the maternal brain may represent a developmental endpoint in mammals. Structural changes in mothers across various regions (Leuner and Gould, 2010; Shams et al, 2012) suggests widespread CNS developmental and plasticity events occur in mothers.…”
Section: Cns Development Plasticity Neurogenesis and Differentisupporting
confidence: 88%
See 2 more Smart Citations
“…This finding is consistent with enrichment analysis within specific regions (Eisinger et al, 2013b, 2014; Driessen et al, 2014b; Zhao et al, 2014) and suggests that the maternal brain may represent a developmental endpoint in mammals. Structural changes in mothers across various regions (Leuner and Gould, 2010; Shams et al, 2012) suggests widespread CNS developmental and plasticity events occur in mothers.…”
Section: Cns Development Plasticity Neurogenesis and Differentisupporting
confidence: 88%
“…In recent studies, we used high density microarrays that allowed for assessment of over 20,000 protein coding genes to assay gene expression changes in the postpartum CNS in four brain regions that contribute to the maternal phenotype: medial preoptic area (MPOA) (Driessen et al, 2014b), medial prefrontal cortex (mPFC) (Eisinger et al, 2014), lateral septum (LS) (Eisinger et al, 2013b), and nucleus accumbens (NAC) (Zhao et al, 2014). In these studies we compared the CNS of maternal to virgin mice and typically identified over 1000 genes per region with significant alterations in expression, suggesting a high level of change in the postpartum condition.…”
Section: Synthesis Of Recent Multiple Large Scale Gene Expression mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies comparing wide-scale gene expression in postpartum and virgin rats, specifically in brain regions thought to be involved in parenting (e.g. MPOA, medial prefrontal cortex), support the notion that subsets of genes regulating maternal behavior and maternal memory are also implicated in psychopathologies like social disorders, depression, psychosis, and bipolar disorder Eisinger et al, 2014;Zhao et al, 2014). Thus the neural plasticity required during the normal shift to parenting also puts mothers at risk for mental health disorders often associated with the postpartum period.…”
Section: Other Genetic Pathwaysmentioning
confidence: 88%
“…As a notable example, the rBEE at chromosome 6:21587723-21589288, which had a high M1 module membership (kME = 0.84; Online Methods), is located approximately 5 kb upstream of SOX4 and is most highly coexpressed with SOX4 and FABP7. SOX4 encodes a transcription factor important for neuronal differentiation 46 , and FABP7 has been recently implicated in ASD by gene expression studies, mutational analyses and mouse model studies [47][48][49] . In addition, the top 20 genes coexpressed with the rBEE at chromosome 6:21587723-21589288 also include AUTS2, which is associated with susceptibility to autism (Fig.…”
Section: Identification Of Rbeesmentioning
confidence: 99%